An Evaluation of User Experience for 360° UPN Virtual Tour - Tri Lathif Mardi Suryanto; Nur Cahyo Wibowo; Kevin Khanza Pangestu (Nusantara Science and Technology Proceedings, 2022)
Thanks to the digital transformation that we often encounter today, many things that were previously unthinkable to do are now becoming a reality. Virtual tours allow users to come to a place and see their surroundings without having to come there. Various images to videos that are combined to produce a 360° panorama can be used through devices such as computers to smartphones. This advantage was used by Universitas Pembangunan Nasional “Veteran” Jawa Timur. as a step in branding its campus so that it could show the location of the campus without having to come directly there, especially during this pandemic which does not allow everyone to gather in one place directly. Because the UPN Vtour is an important asset for the campus to be able to introduce it to prospective students and their parents, it must be ensured that users get a good user experience. For this reason, a study was conducted to evaluate user experience in using UPN Vtour based on the User Experience Questionnaire (UEQ) which was distributed to 72 students of UPN “Veteran” Jawa Timur. Information System and then analyzed using the Structural Equation Model (SEM) technique. The results show that reliability and simulation are the main attractions, while others need to be developed again.